The making of a scribe : errors, mistakes and rounding numbers in the Old Babylonian Kingdom of Larsa /: errors, mistakes and rounding numbers in the Old Babylonian Kingdom of Larsa. (©2020) - Middeke-Conlin, Robert
No abstract available